RESPON PERTUMBUHAN SEMAI KEMIRI (Aleurites moluccana Willd.) TERHADAP INOKULASI BEBERAPA SPESIES FUNGI MIKORIZA ARBUSKULAR - Rinti, Darwis K; Yusran, Yusran; Irmasari, Irmasari (Universitas Tadulako, 2015)
A study on the effects of three fungi mycorrhizal arbuscular (FMA) species on the growth of Aleurites moluccana Willd. Seedlings was conducted at the farmers group nursery, Uwemanje village, Kinovaro district, Sigi regency, Central Sulawesi. The purpose of this research was to know the effects of three FMA species on the growth of A. moluccana Willd. Seedlings. The experiment was laid out in a Randomized Complete Design(RCD) consist of three treatments; without mycorrhizal inoculation/control (M0), Glomus mosseae (M1), Glomus etunicatum (M2) and Glomus deserticola (M3). Five replication of each treatment combination was used for this study. Observation Parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant, fresh weight of shoot and root, dry weight of shoot and root, and seedling quality index. The results showed that inoculation of FMA species had significant effect on the seedling height increment, stem diameter increment and increment of leaf number per plant, fresh weight of shoot and root and dry weight of shoot and root. The highest growth parameters was achieved by Glomus mosseae inoculation compared to Glomus etunicatum, Glomus deserticola and control treatments. Therefore, G. mosseae species is recommended for bio-fertilizer at nursery stage to improve early growth of seedlings. Keywords : Fungi Mycorrhizal Arbuscular, Seedling growth, Aleurites moluccana Willd.